2005
DOI: 10.1002/jcb.20437
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of calcineurin in human colorectal adenocarcinomas

Abstract: Colorectal cancer (CRC) is the third most common cause of cancer death in the Western world. Calcineurin (CaN), a Ca2+/calmodulin (CaM)-dependent protein phosphatase, is important for Ca2+-mediated signal transduction. The main objective of this study is to examine the potential role of Ca2+/CaM-dependent protein phosphatase in both normal and in invasive tumor components of human samples. In this study, we carried out 45 cases of CaN activity, 13 cases of CaN protein expression by Western blot analysis, and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
66
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 43 publications
4
66
0
Order By: Relevance
“…The correlation between expression of the proteins in normal-appearing peritumoral gastric mucosa and cancer tissue with each other. downregulation of calpastatin was observed (17). In human prostate cancer, the mRNA level of CAPN1 increased (22).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The correlation between expression of the proteins in normal-appearing peritumoral gastric mucosa and cancer tissue with each other. downregulation of calpastatin was observed (17). In human prostate cancer, the mRNA level of CAPN1 increased (22).…”
Section: Discussionmentioning
confidence: 95%
“…Calpain has been reported to be involved in apoptosis of cancer cells (15). In addition, the upregulation of calpain may be involved in cancer development and migration (16), and calpain expression is upregulated in a number of tumors, including colorectal adenocarcinoma (17), breast cancer (18) and ovarian cancer (19). In GC, it has been reported that the calpain activity was upregulated compared with normal tissue (20), and it is speculated that higher calpain and calpastatin expression may be a favorable prognostic marker for GC (21).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of calpastatin has not been previously studied in prostate tumors. However, an increase in the calpain/calpastatin ratio has been reported in a study of colorectal cancer (31), which showed that calpastatin levels are high in normal mucosa but decreased in tumor tissue. Moreover, increased expression of calpain 2 was detected in colorectal tumors and polyps, suggesting that the increase of calpain 2 levels may be an early event in the tumorigenesis process.…”
Section: Discussionmentioning
confidence: 96%
“…In mitochondrial DNA-depleted human lung carcinoma A549 cells, the cell morphology is altered while invasive behavior and the increased expression and activity of CaN could be observed (Amuthan et al, 2002). In addition, higher levels of CaN protein and activity are observed in human colorectal adenocarcinomas and neuronal tumors (Goto et al, 1987;Lakshmikuttyamma et al, 2005). However, information regarding the mechanism in which CaN-overexpression causes the formation of human tumors has been limited.…”
Section: Introductionmentioning
confidence: 99%